Long-Term Industrial Labor Demand Forecast for Hungary - John Sutherland Earle; Álmos Telegdy (Hungarian Academy of Sciences, Institute of Economics, 2011)
This study forecasts the Hungarian labor demand for 10 broad economic sectors for 2020. Using aggregate data for the period of 1992-2010 and a structural macroeconomic model, we find that the relative importance of agriculture and industry is likely to fall in total employment while the share of construction, trade and financial intermediation will increase.
Keywords: C530; J21; J23; 330; labor demand; forecasting; Hungary; Arbeitsmarktprognose; Arbeitsnachfrage; Branche; Makroökonomik; Ungarn